Adsorption Efficiency of Iron Modified Carbons for Removal of Pb(II) Ions from Aqueous Solution - Mohammad Hossein Salmani; Mohammad Abedi; Seyed Ahmad Mozaffari (Shahid Sadoughi University of Medical Sciences, 2016)
Abstract Introduction: The Lead causes severe damage to several systems of the body, especially to bony tissues. Until now, several low-cost biosorbents have been studied for removal of heavy metal ions from aqueous solutions. In the present study, carbonized pomegranate peels modified with Fe2+ and Fe3+ ions and then it was investigated for removal of Pb(II) ions from aqueous solution. Materials and methods: the washed granola of pomegranate peel was separately socked with FeCl3 and FeCl2 solutions for 24 h. Then, the granules were carbonized at 400 ºC for 3 h in a programmable furnace in the atmosphere of nitrogen. The adsorption experiments were carried out for two types of iron-modified carbons by batch adsorption using one variable at a time procedures. Results: The optimum conditions were found as contact time 90 min, initial concentration 50 mg/l, and adsorbent dose, 1.00 g/100 ml solution. Maximum removal efficiency was calculated as 84% and 89% for Fe3+ and Fe2+ impregnated pomegranate peel carbons respectively. Conclusion: The iron treatment pomegranate peel carbons modified their surfaces for adsorption of heavy metals. The results showed that chemical modification of the low-cost adsorbents originating from agricultural waste has stood out for metal removal capabilities.